THE INFLUENCE OF USING DICTIONARY AND CONTEXT CLUE STRATEGY ON VOCABUALRY MASTERY AT THE FIFTH SEMESTER - Lollo Rosa Lubis; Nina Nurbaidah; Aprida Irmayana (Jurnal Education and Development, 2021)
The aim of this study to describe what percentage the influence of using dictionary and context clue strategy on vocabulary mastery at the fifth semester students of English Department of Institut Pendidikan Tapanuli Selatan. The research was conducted by applying quantitative descriptive with 20 students as the sample for using dictionary and 20 students for using context clue strategy. They were taken by using random sampling technique. Questionnaire and test were used in collecting the data. the result shows (1) using dictionary strategy gives 42.9% on vocabulary mastery, (2) using context clue strategy gives 23.7% on vocabulary mastery , and (3) using dictionary is better than context clue strategy on vocabulary mastery at the fifth semester students of English Department of Institut Pendidikan Tapanuli Selatan.